Hubungan Intensitas Kebisingan Dengan Frekuensi Denyut Nadi Pada Tenaga Kerja Pabrik Tahu di Jalan K. L. Yos Sudarso Km 7,5 Mabar Medan Tahun 2013 - parta sulaiman (Lingkungan dan Kesehatan Kerja, 2014)
Noise is one part of the work environment that can affect the productivity of a worker . High intensity noise can also speed up the heart rate, raise blood pressure and in the long term will burden the heart and can cause stress that eventually lead to fatigue . The purpose of this study was to determine the intensity and of pulse rate and determine the relationship of the intensity of the noise with a pulse rate on labor Tofu Factory Jl K. L. Yos Sudarso Km 7.5 Mabar , Medan in 2013 . The research is this research to design cross - sectional . The population is all workers who work in the factory knows Nuts Mas , as many as 16 people and the entire population sampled this study . Based on the results of research using Pearson Product Moment Correlation test indicated that the intensity of noise exposure with a pulse in the time before work proceeds obtained p value = 0.034 to p ≤ 0.05 . For the pulse rate at rest , the results obtained so p value = 0.029 p ≤ 0.05 . And the pulse rate of the time after work the results obtained p value = 0.027 to p ≤ 0.05 . So that the noise intensity is expressed significantly associated with the pulse rate. It is expected to the company that paid more attention to the feasibility conditions and the working environment for workers to use personal protective equipment when working . For the next researcher to use different variables in order to obtain more valid research results and increase the number of respondents surveyed . Keywords : Noise, Pulse Rate, Kacang Mas Tofu Factory